First Human Use of a New Robotic-Assisted Fiber Optic Sensing Navigation System for Small Peripheral Pulmonary Nodules - Fielding, David I.K.; Bashirzadeh, Farzad; Son, Jung Hwa; Todman, Maryann; Chin, Adrian; Tan, Lionel; Steinke, Karin; Windsor, Morgan N.; Sung, Arthur Wai (Respiration, 2019)
Background: We tested a new, investigational robotic-assisted bronchoscope system with a remotely controlled catheter to access small peripheral bronchi with real-time driving under live visualization and distal tip articulation of the catheter. The unique catheter remains stationary once located at the biopsy position. Objectives: The primary objectives of this study were to evaluate the safety and feasibility of a new shape-sensing robotic bronchoscope system to bronchoscopically approach and facilitate the sampling of small peripheral pulmonary nodules of 1–3 cm. Secondary objectives included evaluating procedural characteristics and early performance trends associated with the use of the new robotic bronchoscope system. Methods: Subjects were enrolled according to study eligibility criteria at a single center. Navigation pathways were semi-automatically created using pre-procedure CT scans. Simultaneous (real-time) viewing of actual and virtual bronchi was used real time during navigation to the displayed target. An endobronchial ultrasound mini-probe was used to confirm lesion location. Flexible 19- to 23-G needles specifically designed to accommodate tight bend radii in transbronchial needle aspiration were used along with conventional biopsy tools. Enrolled subjects completed follow-up visits up to 6 months after the procedure. Results: The study included 29 subjects with a mean lesion size of 12.2 ± 4.2, 12.3 ± 3.3, and 11.7 ± 4.1 mm in the axial, coronal, and sagittal planes, respectively. The CT bronchus sign was absent in 41.4% of cases. In 96.6% of cases, the target was reached, and samples were obtained. No device-related adverse events and no instances of pneumothorax or excessive bleeding were observed during the procedure. Early performance trends demonstrated an overall diagnostic yield of 79.3% and a diagnostic yield for malignancy of 88%. Conclusion: This new robotic-assisted bronchoscope system safely navigated to very small peripheral airways under continuous visualization, and through maintenance of a static position, it provides a unique sampling capability for the biopsy of small solitary pulmonary nodules.